Efficient ladle furnace refining method based on thin-slab casting and rolling production of high-strength steel - LIU ZHIYONG; QI JIANGHUA; TAO WENZHE; PENG ZHUGANG; HUANG DAWEI; CHEN JIQING (2017)
The invention discloses an efficient ladle furnace refining method based on thin-slab casting and rolling production of high-strength steel. The efficient ladle furnace refining method is characterized in that in a converter tapping stage, the converter tapping temperature ranges from 1,680 DEG C to 1,700 DEG C; quick oxygen probing is performed on molten steel in an argon station, and the addition of aluminum is determined according to the oxygen content; the ingredients and the alkalinity of an appropriate slag system are determined in the ladle furnace slagging stage; in the ladle furnace heating stage, after molten steel arrives at a station, a lower electrode heats up the molten steel, the heating power is controlled in a segmented manner, crusting on the slag surface is realized in the earlier stage, and slugging is performed at low gear; and after melting of slag, the slag surface is uniformly coated, heating is performed at high gear, point heating is adopted in the later stage, and one-time heating i